Social Interaction as a Determining Factor of Friendship Quality in the Novel Melangkah by Js Khairen. - Inayah Nuraulia Mokodongan; Sitti Rachmi Masie; Herman Didipu (Jurnal Pembelajaran Bahasa dan Sastra, 2026)
Friendship is a fundamental social institution that serves as a forum for social interaction and psychological support for adolescents and young adults. This study examines the determinants of friendship quality in JS Khairen's novel "Melangkah" (Step Away) using a sociology of literature approach and descriptive qualitative methods. The analysis focuses on the formation of authentic friendships through the dynamics of intensive interactions between the characters Arif, Siti, Ocha, and Aura as they face various crises. The results show that friendship quality is determined by the synergy of three main factors. First, individual factors include complementary personality traits such as Siti's self-confidence and Arif's composure, a shared interest in pencak silat, and prosocial moral values ??that transform vulnerability into collective strength. Second, situational factors, such as survival experiences in extreme places like caves in Sumba, act as a powerful catalyst, transforming ordinary relationships into bonds of solidarity that withstand crises and provide mutual protection. Third, environmental factors include adaptation to Sumbanese local wisdom, a sincere acceptance of economic limitations with an anti-materialist approach, and the constructive use of social media for social contribution. This study aims to analyze the determinants of authentic friendship quality in JS Khairen's novel "Melangkah" (Step Away) using a sociological approach. Furthermore, this research is expected to provide practical insights as a reference for improving the quality of social interactions in real life.